2002
DOI: 10.1128/aem.68.2.784-790.2002
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Exopolysaccharide Production by Metabolic Engineering of Streptococcus thermophilus

Abstract: It is possible that the low levels of production of exopolysaccharides (EPSs) by lactic acid bacteria could be improved by altering the levels of enzymes in the central metabolism that influence the production of precursor nucleotide sugars. To test this hypothesis, we identified and cloned the galU gene, which codes for UDP glucose pyrophosphorylase (GalU) in Streptococcus thermophilus LY03. Homologous overexpression of the gene led to a 10-fold increase in GalU activity but did not have any effect on the EPS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
79
1
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(83 citation statements)
references
References 38 publications
2
79
1
1
Order By: Relevance
“…EPS yields have been enhanced in S. thermophilus by overexpressing genes coding for the Leloir enzymes (Levander et al, 2002;Svensson et al, 2005). EPS biosynthesis pathways and regulation mechanisms are generally complex, and enhancement of EPS production when metabolizing lactose may not be explained only by sugar nucleotide biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EPS yields have been enhanced in S. thermophilus by overexpressing genes coding for the Leloir enzymes (Levander et al, 2002;Svensson et al, 2005). EPS biosynthesis pathways and regulation mechanisms are generally complex, and enhancement of EPS production when metabolizing lactose may not be explained only by sugar nucleotide biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…To increase EPS production, metabolic engineering has been attempted to overcome regulation in the basal metabolic reactions involved in sugar nucleotide biosynthesis in Lactococcus lactis and Streptococcus thermophilus (Boels et al, 2001a(Boels et al, , 2003aLevander & Rådström, 2001;Levander et al, 2002;Looijesteijn et al, 1999). EPS yields have been enhanced in S. thermophilus by overexpressing genes coding for the Leloir enzymes (Levander et al, 2002;Svensson et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Due to competition, a reduction in growth was observed with increasing EPS production. 28,29) There is a report the induction of EPSs under salt stress conditions, the desert soil alga Microcoleus vaginatus Gom. It was found that the presence of NaCl in the culture led to an accumulation of low molecular weight carbohydrates.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic engineering strategies could be applied to one or more of those stages involved in the EPS biosynthesis in order to increase the EPS production or to modify its composition, however, until now only strains of L. lactis and Streptococcus thermophilus have been genetically modified to enhance EPS biosynthesis. In S. thermophilus the modification of the levels of the GalU, PgmA and the Leloir route enzymes resulted in increased levels of EPS (Levander et al, 2002). Homologous overexpression of a complete eps operon in L. lactis resulted in about fourfold increase in EPS production (Boels et al, 2003).…”
Section: Exopolysaccharides (Eps) Productionmentioning
confidence: 99%